Pharmacological Profile of the Novel Anti-inflammatory Corticosteroid NS-126, a Therapeutic Agent for Allergic Rhinitis - Naoki Inoue; Asami Hashino; Kiyoto Kageyama; Xin Zhang; Takahiro Sasagawa; Naoko Kawakita; Yosuke Takahashi; Katsumi Yoshida; Mikiko Hashimoto; Kazuya Mori; Takashi Kyoi (Elsevier, 2010)
NS-126 (9-fluoro-11β,17,21-trihydroxy-16α-methylpregna-1,4-diene-3,20-dione 21-cyclohexanecarboxylate 17-cyclopropanecarboxylate) is a novel, highly lipophilic anti-inflammatory corticosteroid. We compared NS-126 and the widely used intranasal corticosteroid fluticasone propionate (FP) in a guinea-pig model of allergic rhinitis and a rat model of airway eosinophilia. In the allergic rhinitis model, NS-126 and FP reduced sneezing and nasal obstruction to similar extents. In the airway eosinophilia model, both compounds inhibited the infiltration of eosinophils into the bronchoalveolar lavage fluid, but the effect of NS-126 was longer-lasting than that of FP. In vitro, NS-126 showed lower affinity than FP for the glucocorticoid receptor and was a weaker inhibitor of Th2 cytokine and chemokine production and mast-cell secretory responses. We also investigated DX-17-CPC, a metabolite of NS-126 generated in nasal tissue by carboxylesterasecatalyzed hydrolysis at the 17-position. DX-17-CPC showed greater affinity than NS-126 for the glucocorticoid receptor and was a stronger inhibitor of Th2 cytokine and chemokine production and mast-cell secretory responses. The long duration of the anti-allergic effects of NS-126 may be explained by its high lipophilicity, while the strength of its anti-allergic effects may be explained by the generation of the active metabolite DX-17-CPC. NS-126 is a long-acting intranasal corticosteroid and a promising therapeutic agent for allergic rhinitis. Keywords:: NS-126, dexamethasone cipecilate, DX-17-CPC, lipophilicity, allergic rhinitis